2021
DOI: 10.1002/ange.202104075
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of Chemical Reactivity for Surface‐Confined Ru‐Porphyrins

Abstract: We assess the crucial role of tetrapyrrole flexibility in the CO ligation to distinct Ru-porphyrins supported on an atomistically well-defined Ag(111) substrate.O ur systematic real-space visualisation and manipulation experiments with scanning tunnelling microscopyd irectly probe the ligation, while bond-resolving atomic force microscopya nd X-ray standing-wave measurements characterise the geometry,X-ray and ultraviolet photoelectron spectroscopyt he electronic structure,a nd temperature-programmed desorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…It is therefore reasonable to assign this component to IMe desorption from the transported Ru‐TPP molecules and to the reintegration of those Ru‐TPP molecules back into the compressed phase. This is in good accord with the stronger binding of ligands to the Ru‐TPP adlayer vs. to Ru‐TPP in direct contact with Ag(111) observed experimentally for CO [14e] . Indeed, DFT calculations find an energy difference of 1.05 eV between the bond strength of IMe to the isolated Ru‐TPP molecule vs. to Ru‐TPP adsorbed on Ag(111).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…It is therefore reasonable to assign this component to IMe desorption from the transported Ru‐TPP molecules and to the reintegration of those Ru‐TPP molecules back into the compressed phase. This is in good accord with the stronger binding of ligands to the Ru‐TPP adlayer vs. to Ru‐TPP in direct contact with Ag(111) observed experimentally for CO [14e] . Indeed, DFT calculations find an energy difference of 1.05 eV between the bond strength of IMe to the isolated Ru‐TPP molecule vs. to Ru‐TPP adsorbed on Ag(111).…”
Section: Resultssupporting
confidence: 84%
“…The trans ‐effect is documented upon ligation of several inorganic molecules on metalloporphyrins and phthalocyanines. In particular, a substantial structural trans ‐effect is observed on the Ru‐TPP/Ag(111) upon CO ligation: the Ru atoms are displaced 0.6 Å further away from the Ag interface, while they remain very close to their initial adsorption sites [14e] . In contrast, the strong registry on Ag(111) hollow sites is not found after IMe ligation in the DFT optimised geometries (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,2 ] The supporting interface further introduces the possibility of catalyzing confined reactions that alter the molecular conformation, e.g., thermally‐activated porphyrin dehydrogenation, and turn out to influence the chemical reactivity and magnetic properties of porphyrin molecules. [ 3–5 ] In this regard molecular devices supported at well‐defined interfaces attainable by covalent on‐surface confined polymerization may further benefit from the improvement of their stability and optoelectronic properties. [ 6,7 ] It was further demonstrated that the single ion configuration is uniform across covalently extended porphyrin structures.…”
Section: Introductionmentioning
confidence: 99%